PERANCANGAN WEBSITE PENDUKUNG KEPUTUSAN PENGURUS TERBAIK UKKI UPN JATIM MENGGUNAKAN MODEL WATERFALL - Nesvia Nissa Artanti; Abdul Rezha Efrat Najaf; Tri Luhur Indayanti Sugata (CV. Adiba Aisha Amira, 2026)
UKKI UPN Veteran Jawa Timur requires an objective and transparent mechanism to determine the best management board members in each organizational period. The evaluation process previously relied on manual calculations using spreadsheets, which was considered ineffective, difficult to interpret, and prone to human error and subjectivity. This study aims to design and develop a web-based Decision Support System (DSS) to assist in selecting the best management board members in a systematic and accurate manner. The research adopts a qualitative approach to identify system requirements through interviews with the general chairman, general secretary, and several relevant stakeholders. System development is conducted using the Waterfall model, which consists of requirements analysis, system design, implementation, testing, deployment, and maintenance stages. The Decision Support System applies the Analytical Hierarchy Process (AHP) to determine criteria weights and the Weighted Product (WP) method to rank the alternatives. The results show that the developed website is capable of managing member data, evaluation criteria, assessment scores, and organizational periods, as well as presenting ranking results in real time. The system enhances efficiency, accuracy, and transparency in determining the best management board members at UKKI UPN Veteran Jawa Timur.